Illumination of Divine Love: Rediscovering the Hikmats of Sufi Ahmad Yasawi - Juraev, Zuhriddin; Ahn, Young-Jin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
Divine love, rooted in religious and spiritual traditions, remains relevant today as it represents unconditional, selfless love and fosters empathy, compassion, and understanding among individuals. Embracing the principles of divine love can promote unity, tolerance, and interdependence, fostering global harmony and peace. This study uses a philosophical framework to examine the complex concept of divine love, specifically looking at the historical development and subtle meanings of love-related terms in Islamic Sufi literature. Special attention is given to Sufi poetry, specifically the works of the renowned mystic Shaykh Ahmad Yasawi and his 12th-century collection, Devon-i Hikmat or Hikmats, which are highly respected in Turkish culture. The research explores the stages of love and offers philosophical interpretations to understand the complex implications and profound nature of this concept. This study enhances our understanding of Sufi literature’s perspective on divine love by emphasizing its enduring significance as a universal and timeless facet of human experience that transcends temporal and cultural boundaries. Consequently, it fosters a profound understanding and appreciation for the enduring themes and cultural heritage found in Turkic Sufi poetry. The research highlights the lasting significance of divine love and the cultivation of deep respect for the timeless themes and rich cultural heritage found in Turkic Sufi poetry.